2007
DOI: 10.1101/lm.566007
|View full text |Cite
|
Sign up to set email alerts
|

Protection from premature habituation requires functional mushroom bodies in Drosophila

Abstract: Diminished responses to stimuli defined as habituation can serve as a gating mechanism for repetitive environmental cues with little predictive value and importance. We demonstrate that wild-type animals diminish their responses to electric shock stimuli with properties characteristic of short-and long-term habituation. We used spatially restricted abrogation of neurotransmission to identify brain areas involved in this behavioral response. We find that the mushroom bodies and, in particular, the ␣/␤ lobes app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 72 publications
5
70
1
Order By: Relevance
“…Alternatively, or additionally, CS onset may influence the salience of a following US, and this effect may decrease with increasing CS-US intervals. In Drosophila, the habituated response to a US (electroshock) can be dishabituated by odor stimulation, showing that odors can indeed increase US salience (Acevedo et al, 2007). Such a CSmediated increase in the US salience would also explain the improved memory acquisition that we found when a second odor stimulus was placed into the CS-US gap (Fig.…”
Section: Features Of Trace-memory Acquisitionsupporting
confidence: 57%
“…Alternatively, or additionally, CS onset may influence the salience of a following US, and this effect may decrease with increasing CS-US intervals. In Drosophila, the habituated response to a US (electroshock) can be dishabituated by odor stimulation, showing that odors can indeed increase US salience (Acevedo et al, 2007). Such a CSmediated increase in the US salience would also explain the improved memory acquisition that we found when a second odor stimulus was placed into the CS-US gap (Fig.…”
Section: Features Of Trace-memory Acquisitionsupporting
confidence: 57%
“…Habituation or sensitization to a noxious stimulus could be regulated by the circadian clock so that while the same training protocol may be used at all times of day, the salience of the US or the aversive odor used as the CS+ may be different. Recent research has shown habituation to electric shock occurs in flies and is dependent upon and modulated by the MBs (Acevedo et al 2007a). Similarly, electric shock can induce nonassociative decreases in olfactory responsiveness (Acevedo et al 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, male flies also learn to attenuate their courtship behavior after experiencing rejection by a fertilized female (Kamyshev et al, 1999;Siegel & Hall, 1979). Procedures have been developed to study habituation and sensitization (Acevedo et al, 2007;Duerr & Quinn, 1982). Recent studies in Drosophila have revealed that flies may exhibit attention-like processes (van Swinderen & Flores, 2007), goal-driven behavioral adaptations (Pick & Strauss, 2005), and decision making (Zhang et al, 2007).…”
Section: Communicative Signalsmentioning
confidence: 99%